Programmable Common Baseband Modulator for Software Defined Radio system. (1st January 2011) - Hatai, Indranil; Chakrabarti, Indrajit
In Software Defined Radio (SDR), a single hardware structure can be reused to conform to different standards by simply changing some parameter. A low-power, high-speed, low-area parameter-controlled Common Baseband Modulator (CBM) architecture has been proposed in this paper. Using control parameters, the proposed CBM can be configured to support Gaussian Minimum Shift Keying (GMSK) as well as Frequency Modulation (FM) schemes. The design, which is fully pipelined, can operate at a maximum data rate of 276 Mbps. The proposed CBM consumes maximum dynamic power of 108.41 mW when running at 100 Mbps and using only 22.7 kilo equivalent gates.